Zebrafish heart regenerates after chemoptogenetic cardiomyocyte depletion. Issue 7 (8th February 2021) - Missinato, Maria A.; Zuppo, Daniel A.; Watkins, Simon C.; Bruchez, Marcel P.; Tsang, Michael
Abstract: Background: Zebrafish can regenerate adult cardiac tissue following injuries from ventricular apex amputation, cryoinjury, and cardiomyocyte genetic ablation. Here, we characterize cardiac regeneration from cardiomyocyte chemoptogenetic ablation caused by localized near‐infrared excited photosensitizer‐mediated reactive oxygen species (ROS) generation. Results: Exposure of transgenic adult zebrafish, Tg(myl7:fapdl5‐cerulean), to di‐iodinated derivative of the cell‐ permeable Malachite Green ester fluorogen (MG‐2I) and whole‐body illumination with 660 nm light resulted in cytotoxic damage to about 30% of cardiac tissue. After chemoptogenetic cardiomyocyte ablation, heart function was compromised, and macrophage infiltration was detected, but epicardial and endocardial activation response was much muted when compared to ventricular amputation. The spared cardiomyocytes underwent proliferation and restored the heart structure and function in 45–60 days after ablation. Conclusions: This cardiomyocyte ablation system did not appear to activate the epicardium and endocardium as is noted in other cardiac injury models. This approach represents a useful model to study specifically cardiomyocyte injury, proliferation and regeneration in the absence of whole organ activation. Moreover, this system can be adapted to ablate distinct cell populations in any organ system to study their function in regeneration. Key Findings: Chemoptogenetic ablation of adult zebrafish hearts results in mild cardiac injury. The injured heart undergoes regeneration, but without the activation of other cell types such as the epicardium. This model can offers another acute organ injury model and allows for the study of regeneration in a context that does not involve whole organ activation.